Long-term outcomes of lung transplantation with ex vivo lung perfusion technique - Buttar, Sana N.; Schultz, Hans Henrik L.; Møller-Sørensen, Hasse; Perch, Michael; Petersen, Rene Horsleben; Møller, Christian H. (Frontiers in Transplantation, 2024)
Ex vivo lung perfusion (EVLP) has demonstrated encouraging short- and medium-term outcomes with limited data available on its long-term outcomes. This study assesses 1) EVLP long-term outcomes and 2) EVLP era based sub-analysis in addition to secondary outcomes of recipients with EVLP-treated donor lungs compared with recipients of conventionally preserved donor lungs in unmatched and propensity score-matched cohorts. Double lung transplants performed between January 1st 2012 to December 31st 2021 were included. Total of 57 recipients received EVLP-treated lungs compared to unmatched 202 and matched 57 recipients who were subjected to non-EVLP treated lungs. EVLP group had a significantly lower mean PaO2/FiO2 ratio and significantly higher mean BMI than non-EVLP group in the unmatched and matched cohorts. The proportion of smoking history in unmatched cohort was significantly higher in EVLP group, while similar smoking history was demonstrated in the matched cohorts. No difference was demonstrated in overall freedom from death and re-transplantation between the groups in unmatched and matched cohorts (Unmatched: Hazard ratio (HR) 1.28 (95% CI: 0.79-2.07, P = .32), Matched: HR 1.06 (95% CI, 0.59-1.89), P = .89). In the unmatched cohort, overall freedom from chronic allograft dysfunction (CLAD) was significantly different between the groups (HR 1.64, 95% CI 1.07 – 2.52, P=0.02), however the cumulative CLAD incidence was similar (HR 0.72, 95% CI 0.48 – 1.1, P=0.13). In the matched cohort, the overall freedom from CLAD (HR 1.69 (95% CI, 0.97-2.95, P = .06)) and cumulative CLAD incidence (HR 0.91 (95% CI, 0.37-2.215, P = .83)) were similar between the groups. EVLP era sub-analysis of unmatched cohort in 2012-2014 had significantly higher cumulative CLAD incidence in EVLP group, however this was not demonstrated in the matched cohort. All secondary outcomes were similar between the groups in unmatched and matched cohorts. In conclusion, transplantation of marginal donor lungs after evaluation on EVLP is non- detrimental compared to conventionally preserved donor lungs in terms of mortality, re-transplantation, cumulative CLAD incidence, and secondary outcomes. Although unmatched EVLP era of 2012-2014 had significantly higher cumulative CLAD incidence, no such finding was demonstrated in the matched cohort of the same era.